3. Long lasting coma. Issue 1 (January 2015) - Bagnato, S.; Boccagni, C.; Sant'Angelo, A.; Fingelkurts, A.A.; Gagliardo, C.; Galardi, G.
<x xml:space="preserve">Abstract</x> Coma is usually a transient state occurring as a result of a severe brain injury; generally, patients with coma either progress to a full recovery of consciousness or die. A third and much less common mode of progression is the transition into a vegetative state. In this report we describe a patient who remained in a comatose state for more than one year after a traumatic and hypoxic brain injury. This state, which we refer to as long-lasting coma (LLC), may represent a disorder of consciousness with significantly different features from conventional coma, vegetative state, or brain death. Overall data are described. Clinical, neurophysiological, and neuroimaging data suggest that LLC may represent the most severe consciousness disorder. A multi-level involvement of the ascending reticular activating system (ARAS) is required in LLC. A new type of disorder of consciousness characterized by the persistence of a state similar to coma, resulting from a widespread disruption of the ascending arousal control system, is reported. This description may be useful for identification of other patients suffering from this severe disorder of consciousness and suggests important ethical implications.